PENERAPAN ALGORITMA ROUND ROBIN DAN MODULO PADA LOAD BALANCING WEB SERVER - Andi Anto Diarjo; Dadang Iskandar Mulyana (STIKOM CKI, 2017)
Load balancing web server is one of the ways used to improve the performance and availability of web servers, is to divide the requests dating to multiple servers at once, so that the burden borne by each server lighter. The level of availability bias web server is maintained with the use of load balancing, namely when one server can not serve user requests (server down), then automatically the other server directly replace it, so the user as if not knowing that the server is down. The method used in load balancing is to use round robin algorithm and modulo in the server Internet Information Service. From the analysis of the implementation of load balancing has been done, the system load balancing can be one of the effective and efficient solution to create a reliable system with high availability, in particular web server.